ANALISIS KEGAGALAN TRANSFORMATOR PLTU SUKABANGUN 2x10 MW MELALUI PENGUJIAN DISSOLVED GAS ANALYSIS (DGA) DAN BREAKDOWN VOLTAGE (BDV) - Akhdiyatul Akhdiyatul (Electrical Network Systems and Sources, 2022)
The increasing demand for electrical energy, the performance of the equipment in the power plant also increases. Transformer is a tool that feels the impact, namely the increasing temperature of the conductor inside the transformer. To find out the indications of failure in the transformer, we can test one type of insulation on the transformer, namely transformer oil, by testing the Dissolved Gass Analysis and testing the breakdown voltage (Breakdown Voltage). After testing the DGA, the TDCG results are analyzed, whether they are in accordance with the IEEE 1991 Standard. And the Breakdown Voltage is in accordance with the IEC 60156 Standard (SPLN). Test results in November 2021, the TDCG value is in condition 2 referring to the IEEE 1991 standard, where in conditions This requires vigilance and must determine the allowable loading. And after testing the breakdown voltage of the transformer oil, it is known that the breakdown voltage condition is ≤ 30 kV, if it is adjusted to IEC 60156 standards, the breakdown voltage value of the oil starts to be LOW/NOT GOOD. When the results of the Dissolved Gas Analysis and Break Down Voltage tests are not in accordance with the Standards, it results in a decrease in insulation resistance which causes not optimal power to be supplied to customers. Therefore, to maintain the performance or life time of the transformer itself, maintenance is needed. Treating oil is an effort that must be made to maintain the insulation resistance according to the permitted standards and the transformer can operate optimally.